“Aqui começa o Brasil”: colonização penal, territorialização e fronteirização do rio Oiapoque. 1853-1927 - Samuel Tracol; Arnaud-Dominique Houte (Dialogos, 2020)
The Oyapock River has been the border between France and Brazil since the Treaty of Bern came to resolve a centuries-old dispute between the two states. Only populated by indigenous communities and a few adventurers, the two banks of the river are untouched by any lasting colonial and national settlement before the second half of the 19th century. Penal colonization is the formula adopted by the two states to fill the "void" of a border to be formalized. The criminal models circulate and are reinterpreted by participating with great intensity in the making of the territory.